Perceived Social Support among Breast Cancer Patients in the light of some Variabels - Al-shagran, Hanan; Al-karaki, Yasmin (Jordan Journal of Educational Sciences, 2016)
This study aimed to reveal the level of the perceived social support of breast cancer patients. The sample of the study consisted of (220) patients who attend antenatal clinics and who participate in psychological support program and under treatment at King Hussein Cancer Center in the capital Amman. To achieve the objectives of the study the researchers prepared a scale of perceived social support. The results of the study showed that statistically significant difference between the means of the perceived social support due to all of the following variables (marital status, duration of the disease) and level of perceived social support on the overall scale was high. Wheras, there were no statistical difference attributed to:(age, education level, and stage of therapy).